Dual Microbial Inoculation, a Game Changer? – Bacterial Biostimulants With Multifunctional Growth Promoting Traits to Mitigate Salinity Stress in Spring Mungbean - Kumawat, Kailash Chand; Sharma, Poonam; Nagpal, Sharon; Gupta, R. K.; Sirari, Asmita; Nair, Ramakrishnan Madhavan; Bindumadhava, H.; Singh, Sudeep (Frontiers in Microbiology, 2021)
Soil microbes play a vital role in improving plant growth, soil health, ameliorate biotic/abiotic stress and enhance crop productivity. The present study was aimed to investigate a coordinated effect of compatible consortium [salt tolerating Rhizobium and rhizobacterium with 1-aminocyclopropane-1-carboxylate (ACC) deaminase] in enhancing plant growth promoting (PGP) traits, symbiotic efficiency, nutrient acquisition, anti-oxidative enzymes, grain yield and associated profitability in spring mungbean. We identified a non-pathogenic compatible Rhizobium sp. LSMR-32 (MH644039.1) and Enterococcus mundtii LSMRS-3 (MH644178.1) from salt affected areas of Punjab, India and the same were assessed to develop consortium biofertilizer based on salt tolerance, multifarious PGP traits, antagonistic defense activities and presence of nifH, acds, pqq and ipdc genes. Indole Acetic acid (IAA), P-solubilization, biofilm formation, exo-polysaccharides, siderophore, salt tolerance, ACC deaminase activities were all found highly significant in dual inoculant (LSMR-32+LSMRS-3) treatment compared to LSMR-32 alone. Under saline soil conditions, dual inoculant showed a higher seed germination, plant height, biomass, chlorophyll content and macro & micro-nutrient uptake, than un-inoculated control. However, symbiotic (nodulation, nodule biomass and leghaemoglobin content) and soil quality parameters (phosphatase and soil dehydrogenase enzymes) increased numerically with LSMR-32+LSMRS-3 over Rhizobium sp. LSMR-32 alone. Dual bacterial inoculation (LSMR-32+LSMRS-3) increased the proline content (2.05 fold), anti-oxidative enzymes viz., superoxide dismutase (1.50 fold), catalase (1.43 fold) and peroxidase (3.88 folds) in contrast to control treatment. Decreased Na+ accumulation and increased K+ uptake resulted in favorable K+/Na+ ratio through ion homeostasis. Co-inoculation of Rhizobium sp. LSMR-32 and Enterococcus mundtii LSMRS-3 significantly improved the grain yield by 8.92% and led to superior B: C ratio over Rhizobium sp. alone under salt stress. To best of our knowledge this is perhaps the first field report from Indian soils that largely describes dual inoculation of Rhizobium sp. LSMR-32 and Enterococcus mundtii LSMRS-3 and the same can be considered as a game-changer approach to simultaneously induce salt tolerance and improve productivity in spring mungbean under saline stress conditions.